Viable SARS-CoV-2 in the air of a hospital room with COVID-19 patients. (November 2020) - Lednicky, John A.; Lauzardo, Michael; Fan, Z. Hugh; Jutla, Antarpreet; Tilly, Trevor B.; Gangwar, Mayank; Usmani, Moiz; Shankar, Sripriya Nannu; Mohamed, Karim; Eiguren-Fernandez, Arantza; Stephenson, Caroline J.; Alam, Md. Mahbubul; et al.
Graphical abstract: Highlights: Viable (infectious) SARS-CoV-2 was present in aerosols within the hospital room of COVID-19 patients. Airborne virus was detected in the absence of healthcare aerosol-generating procedures. The virus strain detected in the aerosols matched with the virus strain isolated from a patient with acute COVID-19. Abstract: Objectives: Because the detection of SARS-CoV-2 RNA in aerosols but failure to isolate viable (infectious) virus are commonly reported, there is substantial controversy whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can be transmitted through aerosols. This conundrum occurs because common air samplers can inactivate virions through their harsh collection processes. We sought to resolve the question whether viable SARS-CoV-2 can occur in aerosols using VIVAS air samplers that operate on a gentle water vapor condensation principle. Methods: Air samples collected in the hospital room of two coronavirus disease-2019 (COVID-19) patients, one ready for discharge and the other newly admitted, were subjected to RT-qPCR and virus culture. The genomes of the SARS-CoV-2 collected from the air and isolated in cell culture were sequenced. Results: Viable SARS-CoV-2 was isolated from air samples collected 2 to 4.8 m away from the patients. The genome sequence of the SARS-CoV-2 strain isolated from the material collected by the air samplers was identical to that isolated from the newly admitted patient. Estimates of viable viral concentrations ranged from 6 to 74 TCID50 units/L of air. Conclusions: Patients with respiratory manifestations of COVID-19 produce aerosols in the absence of aerosol-generating procedures that contain viable SARS-CoV-2, and these aerosols may serve as a source of transmission of the virus.